Case report: Isolated axillary lymph node metastasis in high-risk endometrial cancer - Chen, Yi-Ju Amy; Oo, Myoe; Xu, Yiqing (Frontiers in Oncology, 2024)
Introduction Various risks of developing distant metastasis over time exists for both early-stage and advanced-stage endometrial cancer. The occurrence of axillary lymph node metastasis as the first site of recurrence, whether isolated or non-isolated, is uncommon, and there is currently no established treatment guideline for such cases. This study highlights four instances of recurrent endometrial cancer that manifested axillary lymph node metastasis, providing a comprehensive review of their distinctive clinical behavior and the treatment strategies employed. Method We reviewed and compared four cases of recurrent endometrial cancer that developed axillary lymph node metastasis following adjuvant treatment. Patients’ perspectives were discussed. Results All four patients had aggressive endometrial histology, including high-grade serous carcinoma and carcinosarcoma. The stages at presentation were stage I and III, with laparotomy or laparoscopy as the initial surgical approach. Axillary lymph node metastasis was the isolated primary site of recurrence in three cases. Of the three patients with isolated axillary lymph node metastasis, two had long-term survival after aggressive locoregional treatment that comprised of surgery and radiation. Conclusion The occurrence of axillary lymph node metastasis as the first site of recurrence is rare, even in high-risk endometrial cancer. In addition to systemic chemotherapy, aggressive loco-regional treatment can potentially maximize the chance of long-term disease control.